Teacher training and school experience: life stories as education practice (Praxis Educativa, 2026)
This paper shows different aspects of a project in the context of Teacher Training at the Education University of Málaga. It works, through Life Stories, the idea of school” the students have when they start their teacher training studies and the changing experience through the process of critical reflection. It is understood that to open a repertoire of experiences also opens the view about the profession and the kind of action it represents.In short, it shows how Stories of Life can be relevant to generate learning conditions. In this way it takes the construction of shared narratives about the sense and functions of school though particular stories of actors. In this way, it speaks about shared stories to show a place of training as a place of meeting.
Keywords: life stories; teacher training; teaching; school; meeting